SISTEM INFORMASI UNIT KEGIATAN MAHASISWA (UKM) UNIVERSITAS TARUMANAGARA BERBASIS WEB - Adinda Putri; Desy Arisandi; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
The Information System of activity unit or UKM at Tarumanagara University on the Web-Based is an application designed to make easier for student to get all information about UKM so that more people are know and register their self to UKM’s new members and also help UKM to disseminate information and introduce their activities to all students at Untar. The Website uses the Waterfall System Development Life Cycle (SDLC) development methodology. The database used in this application is MySQL. The programming languages used are HTML, PHP and Boostrap Framework. The results of user testing of the application show that the application can be understood and can be used easily